(untitled) (Annals of Medical Research, 2021)
Aim: To investigate the applicability of modified Geneva score which is used to evaluate the clinical probability, with the d-dimer results, to reduce the overuse of pulmonary CT angiography, on patients with suspicion of pulmonary thromboembolism. Material and Methods: A total of 400 patients who had performed pulmonary CT angiography, with the suspicion of pulmonary thromboembolism, in the emergency department, were included in this retrospective study. The clinic and demographic datas of the patients were classified according to the modified Geneva score, and d-dimer values were recorded. Presence of pulmonary thromboembolism was investigated on the pulmonary CT angiography images accessed from Picture Archiving Communication Systems.Results: In a 33 (%8.25) of 400 patients, thromboembolism was detected in the pulmonary CT angiography. 20% (n=1), 8.8% (n=25), and 6.4% (n=7) of the patients, have been diagnosed pulmonary thromboembolism by CT, with the high, intermediate, and low clinical probability, respectively. One hundred ninety-seven (49.25%) out of 400 patients had d-dimer results. One (2.9%) out of 34 patients with a negative d-dimer value had thromboembolism in CT. The sensitivity, specificity, positive predictive value, and negative predictive value were calculated, as 78.8%, 28.1%, 9%, 93.6% of the modified Geneva score, and as 94.7%, 18.5%, 11%, and 97.1% of the d-dimer, respectively.Conclusion: In the diagnosis of pulmonary thromboembolism, modified Geneva score, and d-dimer test have high negative predictive values. Other clinic diagnoses can be considered primarily, in patients have low modified Geneva scores with negative d-dimer results. This may contribute to the reduction of the overuse of pulmonary CT angiography.